The impact of Chinese virtual digital humans on international new media platforms - Hu, Xiao; Rungsrisawat, Somdech (Edelweiss Applied Science and Technology, 2025)
This study examines the influence of Chinese virtual digital humans (VDHs) on overseas new media platforms, addressing how their design characteristics, cultural representation, and communication strategies shape global engagement. Through a mixed-methods approach combining surveys (N=278), exploratory factor analysis, and in-depth interviews (n=25), we identify key drivers of VDH dissemination and audience perceptions. Quantitative results reveal that cultural authenticity and cross-cultural strategies significantly enhance engagement, while qualitative data uncovers a paradox of cultural appeal: audiences simultaneously value yet distrust mediated cultural representations. Findings demonstrate that emotional resonance and interactive potential outweigh hyper-realistic design in driving sustained engagement, challenging prevailing industry practices. The study contributes novel insights by proposing a dual-axis model of digital cultural diplomacy (cultural authenticity × strategic adaptability) and revealing audience agency in hybridizing cultural meanings. Practical implications include prioritizing narrative depth over visual fidelity and establishing ethical guidelines for AI-mediated cultural representation. This research advances theoretical frameworks in digital globalization while offering actionable strategies for creators deploying VDHs in cross-cultural contexts.